Sex differences in long‐term cardiovascular outcomes among patients with acute myocardial infarction: A population‐based retrospective cohort study. Issue 5 (4th March 2021) - Chang, Shih‐Sheng; Lin, Shih‐Yi; Lai, Jung‐Nien; Chen, Ke‐Wei; Lu, Chiung‐Ray; Chang, Kuan‐Cheng; Chiu, Lu‐Ting; Kao, Chia‐Hung
Abstract: Background: Whether a sex difference exists in long‐term cardiovascular (CV) outcomes after acute myocardial infarction (AMI) is worth exploration. This study is sought to investigate the relationships among sex, age, and the long‐term prognosis after AMI. Methods: This population‐based retrospective cohort study used Taiwan's National Health Insurance Research Database to investigate the sex differences in in‐hospital and long‐term CV outcomes in patients with AMI. We enrolled patients who were first diagnosed with AMI from January 1, 2000 to December 31, 2013. The outcomes of interest included all‐cause mortality, CV death, non‐fatal stroke, non‐fatal heart failure, and AMI recurrence during hospitalization and 5‐year follow up. The CV outcomes were also analyzed by age stratification. Results: Overall, 201 921 patients with AMI were analyzed; 68.72% were men and 31.28% were women, with mean ages of 65.34 ± 14.12 and 73.05 ± 12.22 years, respectively. Major adverse cardiac events during hospitalization and up to 5 years were consistently greater in women than in men. Multivariable regression analysis revealed no sex difference existed in long‐term all‐cause and CV mortality. Men of all age groups consistently showed higher risk of both short‐ and long‐term recurrence of AMI. Nonetheless, the female sex still independently predicted increased risk of non‐fatal stroke and heart failure from hospitalization until 3‐year follow up. Conclusion: Women with AMI had poorer short‐term and long‐term outcomes. The sex differences in long‐term all‐cause and CV death disappear after multivariate analysis. Nonetheless, female AMI patients independently predicted higher risk of stroke and heart failure from hospitalization until a 3‐year follow‐up. To better understand the pathophysiology of female patients with AMI and develop more effective management, more studies in this field are necessary in the future.